Speech and Swallowing Data in Individual Patients Who Underwent Glossectomy after Prosthetic Rehabilitation. (15th November 2016) - Carvalho, Viviane de; Sennes, Luiz Ubirajara
Abstract : Maintaining oral function in patients undergoing glossectomy boosts interventions such as prosthetic rehabilitation. However, current literature still fails in the presentation of results of prosthetic rehabilitation in relation to speech or swallowing. The objective of this research is to evaluate the effectiveness of prosthetic rehabilitation on voice, speech, and swallowing in patients undergoing glossectomy by performing a systematic literature review and meta-analysis of individual cases. Studies were identified by relevant electronic database and included all dates available. The criteria used were sample with anyn ; resection due to malignant tumors, restricted to tongue and/or floor of mouth; type of prosthetic rehabilitation; and description of the oral functions outcomes with prosthesis. For the meta-analysis of individual data, associations between the variables of interest and the type of prosthesis were evaluated. Thirty-three of 471 articles met the selection criteria. Results on speech and/or voice and swallowing were reported in 27 and 28 articles, respectively. There were improvement of speech intelligibility and swallowing in 96 patients and in 73 patients, respectively, with prosthesis. Based on the available evidences, this article showed that prosthetic rehabilitation was able to improve oral functions and can be a strategy used with surgical reconstruction in selected cases.